Do non-metallic material and radiation shields affect the operation of direct evaporative cooling systems?. (June 2020) - Alamdari, Pedram; Saedodin, Seyfolah; Rejvani, Mousa
Highlights: The performance of a DEC system manufactured by RFX-PSS has been studied. The effect of using radiation shields on DEC systems has been investigated. Using the RFX-PSS-casing instead of metal-casing increases saturation efficiency. Inclined roof increases the saturation efficiency of DEC systems significantly. Glass wool-aluminum radiation shield decreases water consumption of DEC systems. Abstract: The evaporation phenomenon is used as a passive cooling approach to absorb the sensible heat and convert it into the latent heat. The usage of evaporative cooling systems has boomed, recently, because of its low operational cost. The Direct Evaporative Cooling (DEC) systems can be used widely in warm dry environmental conditions, such as Middle East countries. Several factors can affect the DEC system such as water temperature, evaporative cooling pad thickness, air velocity, and solar radiation flux. In this study, the performance and water consumption of evaporative-based cooler manufactured by RFX Polycarbonate-Structured Sheet (PSS) are compared with the metal-casing one. The impacts of tilting the roof of the cooler and attaching a glass wool-aluminum foil on the cooler are evaluated. The assessments show about 20.6% reduction in the usage of water for the case of RFX Polycarbonate-Casing cooler compared to the metallic material. Results also revealed that tilting the roof saves 29% water compared with the metal-casing cooler while changing the inclined roof to the glass wool-aluminum foil radiation shield further saves the water by about 25%. The performance of the RFX-PSS cooler is enhanced by about 4.7% as compared to the metal-casing cooler. The improvement of 8.1% occurs by tilting the roof in RFX Polycarbonate-Casing cooler in comparison with the metallic DEC system and attaching the isolation foil of glass wool-aluminum instead of the inclined roof increases the saturation efficiency by 7%.